2022
DOI: 10.1155/2022/7435477
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of EFL Learners’ Vocabulary Retention and Recall in a Technology-Based Instructional Environment: Focusing on Digital Games

Abstract: Using digital games in language learning is beneficial, but their effectiveness in the Bangladeshi EFL context has been overlooked. Therefore, the purpose of this research was to evaluate the impact of playing digital games on Bangladeshi EFL learners’ ability to remember and retain the language. The Oxford Quick Placement Test was given to 78 Bangladeshi English as foreign language students. Based on the findings, 50 primary school pupils were selected based on the convenient sampling method as the study’s ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Songs influenced positively, especially to vocabulary mastery for children (Sevik, 2014). This findings were in line with the studies recently which claimed that games bring the positive influence on vocabulary Ben El Moudden, 2021; Dashtestani, 2022;Hao et al, 202;Patra et al, 2022). Song used as learning media can provide joy in learning English for children (Fransischa, 2017;Shen, 2009;Hadian, 2015).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Songs influenced positively, especially to vocabulary mastery for children (Sevik, 2014). This findings were in line with the studies recently which claimed that games bring the positive influence on vocabulary Ben El Moudden, 2021; Dashtestani, 2022;Hao et al, 202;Patra et al, 2022). Song used as learning media can provide joy in learning English for children (Fransischa, 2017;Shen, 2009;Hadian, 2015).…”
Section: Resultssupporting
confidence: 85%
“…The efficacy of games occurs for some skills of language. Games bring a positive influence on vocabulary (Ben El Moudden, 2021;Dashtestani, 2022;Hao et al, 202;Patra et al, 2022), grammar (Lin et al, 2020), writing (Fu et al, 2019;Dashtestani, 2022), pronunciation (Dashtestani, 2022), listening (Dashtestani, 2022;Kumar et al, 2022), speaking (Dashtestani, 2022), problem-solving Ben El Moudden, 2021Dashtestani, 2022), motivation (Dashtestani, 2022;Ahmed et al, 2022). These findings indicated that games helped learn English.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations